2002
DOI: 10.1007/bf03402082
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Insulin-Like Growth Factor 2 and Its Receptors in Human Tumors

Abstract: Insulin-like growth factor 2 (IGF-2) is important for normal development and growth of an organism. In humans it is encoded by 11p15.5 paternally expressed imprinted gene. It binds at least two different types of receptors: IGF type 1 (IGF-1R) and IGF-2/mannose 6-phospate receptors (IGF-2R/M6P). Ligand binding to IGF-1R provokes mitogenic and anti-apoptotic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 116 publications
0
27
0
3
Order By: Relevance
“…This finding corroborates previous data where IGF-II LOH (frequently associated with a duplication event; ref. 26) was found in f40% of bladder tumors, including pT a tumors, but was more common in tumors of higher grade and stage (11). Of the four IGF-II imprinting studies in bladder in the literature, LOH was only discussed in one (17) where 1 of 13 (8%) displayed IGF-II LOH.…”
Section: Discussionmentioning
confidence: 99%
“…This finding corroborates previous data where IGF-II LOH (frequently associated with a duplication event; ref. 26) was found in f40% of bladder tumors, including pT a tumors, but was more common in tumors of higher grade and stage (11). Of the four IGF-II imprinting studies in bladder in the literature, LOH was only discussed in one (17) where 1 of 13 (8%) displayed IGF-II LOH.…”
Section: Discussionmentioning
confidence: 99%
“…As their appropriate level and/or interaction regulate cell growth, it is obvious that overexpression of either of them (or both) may be involved in enhanced tumor growth [2]. The proposed mechanism of autocrine IGF 2 action on malignant proliferation came from its elevated secretion by tumors and tumor derived cell lines [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…IGF-IR activation is involved in several processes associated to oncogenic transformation, such as proliferation, migration and invasion (Coppola et al, 1994;Pavelic et al, 2002;Samani et al, 2007;Sell et al, 1994). IGF-I expression rarely occurs in tumoral cells, but can be produced by stromal cells surrounding the tumor.…”
Section: Aberrant Expression Of Igfs In Cancermentioning
confidence: 99%
“…It appears that abnormal IGF-IR activation can result in oncogene activation leading to increased cellular proliferation and malignancy. Although the IGFs are not in themselves tumorigenic factors, it has been shown that overexpression of IGF-II, as in the case of loss of imprinting (LOI) (Pavelic et al, 2002), can contribute to gynaecological malignancies like ovarian cancer (Murphy et al, 2006) and choriocarcinoma (Diaz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%